Donor Allospecific CD44high Central Memory T Cells Have Decreased Ability to Mediate Graft-vs.-Host Disease - Huang, Wei; Mo, Wenjian; Jiang, Jieling; Chao, Nelson J.; Chen, Benny J. (Frontiers in Immunology, 2019)
Data from both animal models and humans have demonstrated that effector memory T cells (TEM) and central memory T cells (TCM) from unprimed donors have decreased ability to induce graft-versus-host disease (GVHD). Allospecific TEM from primed donors do not mediate GVHD. However, the potential of alloreactive TCM to induce GVHD is not clear. In this study, we sought to answer this question using a novel GVHD model induced by T cell receptor (TCR) transgenic OT-II T cells. Separated from OT-II mice immunized with OVA protein 8 weeks earlier, the allospecific CD44high TCM were able to mediate skin graft rejection after transfer to naive mice, yet had dramatically decreased ability to induce GVHD. We also found that these allospecific CD44high TCM persisted in GVHD target organs for more than 30 days post-transplantation, while the expansion of these cells was dramatically decreased during GVHD, suggesting an anergic or exhausted state. These observations provide insights into how allospecific CD4+ TCM respond to alloantigen during GVHD and underscore the fundamental difference of alloresponses mediated by allospecific TCM in graft rejection and GVHD settings.